2018
DOI: 10.1186/s12905-018-0699-5
|View full text |Cite
|
Sign up to set email alerts
|

Trichomonas vaginalis infection and the diagnostic significance of detection tests among Ghanaian outpatients

Abstract: BackgroundThere is little data on Trichomonas vaginalis infection in Ghana. This study evaluated the prevalence of trichomoniasis using different diagnostic methods and determined the risk factors for infection in patients.MethodsA structured questionnaire was administered. Vaginal swabs, urethral swabs and urine specimens were obtained from consenting patients; and the samples processed following standard protocols. The presence of T. vaginalis was determined using wet mount microscopy and polymerase chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 24 publications
2
14
1
Order By: Relevance
“…The finding of this present study is also consistent with a cross-sectional study by Al-Saeed et al who reported a prevalence of 5.4% among a total of 425 vaginal swabs collected from women from Dohok province in Iraq using the culture-based detection method [23]. However, a recent study by Asmah et al in Ghana reported that 64 of 150 outpatients were positive for T. vaginalis [12]. This discrepancy may be due to the fact that Asmah et al included both males and females in their study while only females were included in this present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The finding of this present study is also consistent with a cross-sectional study by Al-Saeed et al who reported a prevalence of 5.4% among a total of 425 vaginal swabs collected from women from Dohok province in Iraq using the culture-based detection method [23]. However, a recent study by Asmah et al in Ghana reported that 64 of 150 outpatients were positive for T. vaginalis [12]. This discrepancy may be due to the fact that Asmah et al included both males and females in their study while only females were included in this present study.…”
Section: Discussionsupporting
confidence: 91%
“…Due to the several detrimental effects associated with the infection, accuracy and precision in clinical diagnosis is essential to reduce the risk of transmission and morbidity. Direct wet-mount microscopic examination is the most used method for T. vaginalis diagnosis, especially in low-and middle-income countries such as Ghana because it is simple and inexpensive [12, 13]. However, direct wet-mount microscopy has low sensitivity and is subject to diagnostic biases as a result of its dependence on operator’s experience and viability of the organism in the specimen [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…First void urine has also been shown to be of added value in diagnosis of trichomoniasis [20] as females may also have urethritis in addition to vaginitis. The usefulness of first void urine also applies to male partners who are infected with Trichomonas vaginalis.…”
Section: Discussionmentioning
confidence: 99%
“…This can be achieved through direct saline wet mount of vaginal secretion. Some authors argue that in few instances, the absence of trichomonads in saline mount microscopy can be a false negative result and may require further processing with a nucleic acid amplification technique, the Polymerase Chain Reaction [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…The accurate diagnosis of trichomoniasis is an important link in the prevention and treatment of the disease, and it is of great significance to prevent the transmission of the disease. At present, the detection methods of T. vaginalis mainly contain wet mount microscopy, PCR, culture, immunofluorescence as well as ELISA [21,22]. Among the diagnostic methods, the wet mount microscopy is low in cost, but poor in sensitivity [23].…”
Section: Introductionmentioning
confidence: 99%